Analysis of Public Perceptions of the Free Nutritious Meal Program in YouTube Comments - Jaizul, Alim; Sandi, Renda (Corespub, 2025)
Public discourse surrounding the Free Nutritious Meal (MBG) program has grown rapidly as the government seeks to improve children’s nutritional intake through large-scale meal distribution. However, various implementation issues such as reports of food poisoning, substandard meal quality, and suspicions of budget mismanagement have raised concerns about the program’s effectiveness and integrity. This study aims to analyze public perceptions of the MBG program using YouTube comments as a data source to understand dominant narratives and sentiment trends. The research employs text preprocessing, N-gram extraction, word cloud visualization, and sentiment analysis using a transformer-based model to evaluate linguistic patterns and emotional polarity. The results show that negative sentiment dominates with 2,242 comments, significantly higher than positive and neutral categories, driven by frequent occurrences of terms such as korupsi, proyek, bocor, and masalah. Word cloud and N-gram findings reveal recurring themes related to food safety, financial transparency, and program implementation gaps.